2023
DOI: 10.1038/s41598-023-32105-6
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse and concentrated nitrogen sewage pollution in island environments with differing treatment systems

Abstract: Macroalgae is an under-utilised tool as a bioindicator of anthropogenic nitrogen loading to the coastal environment in the UK. This study compared two island systems—Jersey (Channel Islands) and St Mary’s (Isles of Scilly) to assess how differing sewerage infrastructure affects nitrogen loading. A total of 831 macroalgae samples of Fucus vesiculosus and Ulva sp. were analysed for nitrogen isotopes (δ15N). Elevated δ15N values were recorded for Jersey (> 9‰) in St Aubin’s Bay—caused by the outflow of the Bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…34,69 Elevated δ 15 N values >+16‰ are rarely recorded in macroalgae studies 45,74 (Gröcke et al , unpub. data), and only a handful of studies have recorded values >20‰, 21,25,45,74 and none previously in the UK. Although BOD assessments indicate that the Mersey Estuary has improved, the Environment Agency reports that it is “not achieving good status” due to industry, 63 with no indication of water detriment from the water industry.…”
Section: Mersey Estuary 2022: a Peak In The Sewage Era?mentioning
confidence: 99%
See 3 more Smart Citations
“…34,69 Elevated δ 15 N values >+16‰ are rarely recorded in macroalgae studies 45,74 (Gröcke et al , unpub. data), and only a handful of studies have recorded values >20‰, 21,25,45,74 and none previously in the UK. Although BOD assessments indicate that the Mersey Estuary has improved, the Environment Agency reports that it is “not achieving good status” due to industry, 63 with no indication of water detriment from the water industry.…”
Section: Mersey Estuary 2022: a Peak In The Sewage Era?mentioning
confidence: 99%
“…It is proposed that the stability of d 15 N in this time interval was a result of stricter controls on discharges, monitoring and increased chemical processing (i.e., ammonia) in wastewater treatment plants. 25,61,72,73 During this time interval, stricter regulations were implemented by the European Union on the UK government to address water quality issues. This legally enforced that the level of nitrate released into freshwater and marine environments be set to a maximum limit of 50 mg l −1 (or 11.3 mg l −1 of nitrate N).…”
Section: Papermentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers highlight the need to establish systems for monitoring the interior to understand the impact of marine ecosystems and biogeochemistry. With an equal focus on the marine system, particularly the coastal one, Alldred et al used macroalgae as a bioindicator of the anthropogenic nitrogen load on the coasts of the United Kingdom 8 . The authors compared two island systems, Jersey (Channel Islands) and St Mary's (Isles of Scilly), to assess how different sewage infrastructure affects nitrogen loading and demonstrated that upgrading sewer systems in the islands is necessary to reduce environmental problems.…”
mentioning
confidence: 99%